Steamboat CASCA with passengers, Yukon River, probably between 1898 and 1911 - University of Washington Libraries. Special Collections Division. (1898)
CASCA was built in 1898 and in 1911, described in company records as being "practically worn out and useless .", she was rebuilt so extensively that she was considered to be a new boat. She was wrecked at Rink Rapids on July 9, 1936. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number